Teaching the integrated management of neonatal and childhood illness: experiences of Lesotho nurse educators: Original Research - Shelile, Mpho Z.; Qhobela, ‘Malihaelo C.; Masakoane, Reentseng Christina (Babali Publisher, 2026)
Introduction: Despite the development of the Integrated Management of Neonatal and Childhood Illness (IMNCI) strategy to reduce child morbidity and mortality and promote optimal child growth and development in low- and middle-income countries, preventable childhood deaths remain a significant public health concern. Evidence suggests that IMNCI is not consistently implemented in clinical practice, partly due to gaps in the pre-service preparation of healthcare providers. Aim: to explore nurse educators’ experiences of teaching the IMNCI strategy in nurse training institutions in Lesotho. Methods: The study adopted a descriptive qualitative design to gain an in-depth understanding of nurse educators’ experiences of teaching the IMNCI strategy. Data were collected through face-to-face interviews and analyzed using Braun and Clarke’s thematic analysis approach, with ethical principles observed throughout the study. Data saturation was achieved after interviewing 12 nurse educators. Results: Three themes emerged from the analysis: the benefits of teaching IMNCI, challenges of teaching IMNCI, and measures to improve teaching of IMNCI. Findings indicate that while IMNCI facilitates the use of diverse pedagogical methodologies, a lack of educator orientation remains a barrier. Consequently, most nurse educators advocate for the formal integration of IMNCI into nursing curricula to standardize its implementation. Conclusion: Teaching IMNCI promotes competency-based learning, clinical decision-making, counseling skills, and rational drug use among nursing students in Lesotho. However, effective teaching is hindered by limited curriculum time, inadequate simulation, inconsistent availability of guidelines, weak clinical integration, and insufficient IMNCI knowledge among educators, nurses, and preceptors, underscoring the need to strengthen IMNCI training.